Polycyclic aromatic hydrocarbons exposure and early miscarriage in women undergoing in vitro fertilization-embryo transfer. (2nd January 2020) - Li, Pei; Hua, Rui; Li, Keyang; Ma, Shengtao; Wu, Biao; Quan, Song; Yu, Zhiqiang
Abstract: Various factors have been reported to be associated with early miscarriages, including microbial infection, chemical toxicity, maternal disorders and genetic abnormalities. In the present study, a prospective cohort study was conducted to investigate whether urinary concentrations of hydroxylated polycyclic aromatic hydrocarbons (OH-PAHs) were associated with early pregnancy loss in women undergoing in vitro fertilization-embryo transfer (IVF-ET). Risk of spontaneous pregnancy loss in patients exposed to PAHs was analysed using 40 patients who had experienced early pregnancy loss compared to 40 who had normal live births. Single spot morning urine samples were collected from each patient 30 days after embryo transfer when clinical pregnancy was confirmed and ten urinary OH-PAHs were measured. After adjustment for age and BMI using a Log Binomial Model, only 2 + 3-PHE was found to be associated positively with early miscarriage. Using Receiver Operating Characteristic (ROC) curve analysis, the Area Under the Curve (AUC) was 0.78 ( p ＜0.001), suggesting that 2 + 3-PHE might provide a potential biomarker to predict the miscarriage risk in patients exposed to high level of PAHs.